2014
DOI: 10.1186/1471-2261-14-94
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of home and daytime ambulatory blood pressure measurements

Abstract: BackgroundHome (HBPM) and ambulatory (ABPM) blood pressure measurements have their advantages and disadvantages in diagnosing and managing hypertension. We studied HBPMs and ABPMs in volunteers taking part in a survey.MethodsOf 366 respondents, 270 provided a total of 5997 triplicate HBPMs ( Part 1 ); 175 also provided data on ABPMs, of which the measurements obtained between 6 am and 10 pm were used in this study (Part 2 ).Results Part 1 , When all 5997 triplicate HPPMs were considered, 1st readings tended t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
2
7
0
2
Order By: Relevance
“…Mean HT duration was 11.56±0.26 years. Measured mean BP was higher at a doctors visit than a noted habitual BP level which can be explained by patient's psychophysiologic reaction to a medical center visit and considered a generally accepted phenomenon [16], however, this leaves open the possibility of underestimation of BP level by the patients in case of its irregular control. The results of the study showed that the majority of the patients had high and very high risk for hypertension-related cardiovascular complications (27.4 and 66.7%, respectively).…”
Section: результаты и обсуждениеmentioning
confidence: 86%
See 1 more Smart Citation
“…Mean HT duration was 11.56±0.26 years. Measured mean BP was higher at a doctors visit than a noted habitual BP level which can be explained by patient's psychophysiologic reaction to a medical center visit and considered a generally accepted phenomenon [16], however, this leaves open the possibility of underestimation of BP level by the patients in case of its irregular control. The results of the study showed that the majority of the patients had high and very high risk for hypertension-related cardiovascular complications (27.4 and 66.7%, respectively).…”
Section: результаты и обсуждениеmentioning
confidence: 86%
“…Средняя длительность АГ составила 11,56±0,26 лет. Среднее измеренное АД на приеме у врача оказалось выше обозначенных цифр привычного АД, что объяснимо психо-физиологической реакцией пациента на посещение лечебного учреждения, и является общепризнанным явлением [16], однако это не исключает возможности недооценки пациентами своего уровня АД в случае нерегулярного контроля. По результатам обследования установлено, что в абсолютном большинстве случаев у пациентов наблюдался высокий и очень высокий риск развития сердечно-сосудистых осложнений АГ (27,4% и 66,7%, соответственно).…”
Section: результаты и обсуждениеunclassified
“…For example, single measurements are insufficient to determine the effects of treatment on blood pressure because of its wide variability (Warren et al , ). Blood pressure measurements should use devices that store the measured values (in duplicate or triplicate) over an appreciable time (e.g., 1 week) so as to provide measures of central tendency and variability at baseline (Chrubasik‐Hausmann et al , ). This should be compared with measurements repeated over a similar time toward the end of treatment (Chrubasik et al , ). Second , outcome assessment should use up‐to‐date technology.…”
Section: Discussionmentioning
confidence: 99%
“…At the last minute of each 4-min interval and 3-min recovery, an expired air gas sample, HR and RPE were measured. Prior, post and 1 h-post-exercise, resting blood pressure was measured by an electronic blood pressure monitor (Boso Medicus, Bosch + SoHn, Jungingen, Germany) after 10 min of supine rest (16). The average of 3 measurements was recorded.…”
Section: Methodsmentioning
confidence: 99%